(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2023)
This paper draws upon Kierkegaard’s deliberations on irony in the context of his lifelong affinity with Socrates over their shared concern with the true meaning of human existence. Aided by contemporary Kierkegaard scholarship, I sketch the notion of therapeutic irony that envisions human beings attaining proper subjectivity and selfhood, thus becoming capable of overcoming the crisis of self-alienation in our present age.